TGF-β promotes microtube formation in glioblastoma through thrombospondin 1 - Joseph, Justin V.; Magaut, Capucine R; Storevik, Simon; Geraldo, Luiz H; Mathivet, Thomas; Latif, Md Abdul; Rudewicz, Justine; Guyon, Joris; Gambaretti, Matteo; Haukas, Frida; Trones, Amalie; Rømo Ystaas, Lars A; et al. (Neuro-Oncology, 2022)
Microtubes (MTs), cytoplasmic extensions of glioma cells, are important cell communication structures promoting invasion and treatment resistance through network formation. MTs are abundant in chemoresistant gliomas, in particular, glioblastomas (GBMs), while they are uncommon in chemosensitive IDH-mutant and 1p/19q co-deleted oligodendrogliomas. The aim of this study was to identify potential signaling pathways involved in MT formation.Bioinformatics analysis of TCGA was performed to analyze differences between GBM and oligodendroglioma. Patient-derived GBM stem cell lines were used to investigate MT formation under transforming growth factor-beta (TGF-β) stimulation and inhibition in vitro and in vivo in an orthotopic xenograft model. RNA sequencing and proteomics were performed to detect commonalities and differences between GBM cell lines stimulated with TGF-β.Analysis of TCGA data showed that the TGF-β pathway is highly activated in GBMs compared to oligodendroglial tumors. We demonstrated that TGF-β1 stimulation of GBM cell lines promotes enhanced MT formation and communication via calcium signaling. Inhibition of the TGF-β pathway significantly reduced MT formation and its associated invasion in vitro and in vivo. Downstream of TGF-β, we identified thrombospondin 1 (TSP1) as a potential mediator of MT formation in GBM through SMAD activation. TSP1 was upregulated upon TGF-β stimulation and enhanced MT formation, which was inhibited by TSP1 shRNAs in vitro and in vivo.TGF-β and its downstream mediator TSP1 are important mediators of the MT network in GBM and blocking this pathway could potentially help to break the complex MT-driven invasion/resistance network.
Early access Oct 2021
Gesehen am 17.11.2022